Selection of financial stimulation instruments of enterprise’s innovation activity in open economy: the case of Ukraine : ст. - Demchyshak, N.; Bahriy, М.; Brychka, B.; Vyslobodska, H. (Ivan Franko National University ; Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2021)
the article's purpose is the priorities justification during the selection of the financial stimulation instruments of the enterprise innovative activities under the conditions of the economic openness. For the research of interdependencies between various indicators it was used the econometrical approaches. Based on analysis of chosen indications with the example of Ukrainian case it is proved that the efficiency of usage the indirect influence instruments is higher in comparison with direct. The importance of national innovation system development was reasoned as a basis for forming of the appropriate level of trust among economical subjects and institutional modernization of the financial regulation system of the innovational activity. The arguments of the conducted research in favor of the indirect instruments usage of innovations financial stimulation in Ukraine are simultaneously the arguments in favor of the creative component development of the national economy. The stress was made on the perspectives of the implementation of the crowdfunding and crowdsourcing instruments for the optimization of enterprise innovational activity structure.
Keywords: enterprise innovative activity; financial stimulation instruments; фінансове стимулювання підприємств